2019
DOI: 10.1126/science.aax5440
|View full text |Cite
|
Sign up to set email alerts
|

Coupled electrophysiological, hemodynamic, and cerebrospinal fluid oscillations in human sleep

Abstract: Sleep is essential for both cognition and maintenance of healthy brain function. Slow waves in neural activity contribute to memory consolidation, whereas cerebrospinal fluid (CSF) clears metabolic waste products from the brain. Whether these two processes are related is not known. We used accelerated neuroimaging to measure physiological and neural dynamics in the human brain. We discovered a coherent pattern of oscillating electrophysiological, hemodynamic, and CSF dynamics that appears during non–rapid eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
767
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(902 citation statements)
references
References 57 publications
49
767
1
5
Order By: Relevance
“…These data suggest that alterations in AQP4-dependent parenchymal CSF flow also have cognitive consequences, unveiled during sleep deprivation. Our data extends the recently described connection between slow waves, neuronal activation and CSF flow in the 4th ventricle (13), by showing that AQP4 haplotype in turn modulate NREM slow wave energy and the restorative effect of sleep on cognitive functions. These observations may indirectly suggest that AQP4 dependent fluid flow within the neuropil is regulated by EEG slow waves during NREM sleep.…”
Section: The Aqp4-haplotype Modulates Subjective and Objective Responsupporting
confidence: 89%
See 1 more Smart Citation
“…These data suggest that alterations in AQP4-dependent parenchymal CSF flow also have cognitive consequences, unveiled during sleep deprivation. Our data extends the recently described connection between slow waves, neuronal activation and CSF flow in the 4th ventricle (13), by showing that AQP4 haplotype in turn modulate NREM slow wave energy and the restorative effect of sleep on cognitive functions. These observations may indirectly suggest that AQP4 dependent fluid flow within the neuropil is regulated by EEG slow waves during NREM sleep.…”
Section: The Aqp4-haplotype Modulates Subjective and Objective Responsupporting
confidence: 89%
“…Increased levels of intracerebral tau and ß-amyloid have been observed in healthy adults after sleep loss (11,12), and recently sleep driven parenchymal CSF pulsations in the fourth ventricle were demonstrated in the human brain (13), providing the first evidence for human glymphatic mechanisms. To date, however, no studies have described the link between AQP4 and human sleep-wake regulation or investigated whether genetic modulation of AQP4 may have restorative effects on cognitive functions after sleep loss.…”
Section: Introductionmentioning
confidence: 97%
“…Several groups have shown that CSF flows between the BM and astrocyte endfeet of arteries and capillaries, with arteriole pulsations driving bulk fluid flow through the parenchyma, although others have argued about the extent of bulk flow (Abbott et al, 2018; Hladky and Barrand, 2019). This “glymphatic” system helps to clear interstitial solutes such as amyloid via paravenous drainage pathways (Iliff et al, 2012; Xie et al, 2013; Mestre et al, 2018) and has been visualized in human patients via magnetic resonance imaging (MRI; Meng et al, 2019; Fultz et al, 2019). Expression of water channel aquaporin-4 in astrocyte endfeet has been reported to play a critical role in the movement of CSF into the parenchyma (Haj-Yasein et al, 2011; Iliff et al, 2012; Mestre et al, 2018).…”
Section: The Nvumentioning
confidence: 99%
“…After washing the interstitial space, the resulting ISF is flushed back outside the brain via veins in the perivascular space. Several factors play a crucial role in the modulation of this clearance system activity, notably sleep and anesthesia, perhaps via a modulation of brain blood volume and pressure [811]. This scheme gives astrocytes a crucial role in controlling water movements between the blood and the brain, through a mechanism dependent on Aquaporin-4 (AQP4), a membrane-bound water channel expressed at their end-feet [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative methods are needed to investigate the glymphatic system non-invasively, especially in the human brain. Fluid-dynamics driven and BOLD fast MRI have the potential to evaluate CSF pulsations in the ventricles and hemodynamics [11,20,21], while IVIM and diffusion MRI have been shown as promising methods for the evaluation of the ISF [7,2224].…”
Section: Introductionmentioning
confidence: 99%